UMP inks MoU with Casablanca Vasity - UMP, PNC (The New Straits Times Press (M) Bhd., 2018)
Kuantan: Universiti Malaysia Pahang (UMP) signed a memorandum of understanding (MoU) with University of Hassan II of Casablanca (l-t2UC) in Morocco to enable the institutions to boost their academic programmes and services.